INDUSTRIAL WASTE MANAGEMENT PRACTICES IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA (Vernoniaamygdalina & Allium sativum extracts) (FUDMA JOURNAL OF SCIENCES, 2022)
This paper examined industrial waste management practices in Kaduna Metropolis, Kaduna State, Nigeria. A mixed method was used in carrying out the study as it involved surveys as well the use of GIS for site suitability. A total of 200 copies of the questionnaire were administered by adopting simple random sampling and used for the analysis. A simple lab test was conducted and findings revealed that there is a wide variation in the levels of zinc and nickel availability, though within the standards for drinking water, suggesting a change in water quality at various locations. High mercury levels in one of the samples are a reason for concern. It was recommended based on the findings amongst others that awareness and education regarding appropriate waste management, including collection and disposal, is essential for all construction workforces and should be provided by firms, in conjunction with the industry, The study recommends that the Kaduna State Government should consider measures, such as the introduction of regulatory policy, including site waste management plan (SWMP), Pay-As-YouThrow (PAYT), and landfill ban to divert material wastes from landfills. PPUV is a Pay-Per-Unit volume of waste generated and its purpose is to reduce waste and encourage reuse and recycling management of industries needs to change the misconception that landfilling is a cheaper option when compared to reuse and recycling. The design team should adopt effective design minimization measures, while other professionals are to ensure efficient waste reduction approaches.
Keywords: Management; PAYT; PPUV; Water; Dumpsite